2004
DOI: 10.1007/s00261-004-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller myotomy and fundoplication: findings and predictive value of early postoperative radiographic studies

Abstract: Radiographic studies are useful for showing leaks after laparoscopic Heller myotomy and fundoplication, but radiologists should differentiate true leaks from trapping of contrast material alongside the fundoplication wrap. The caliber of the esophagus on early postoperative studies is also a useful parameter for predicting short-term clinical outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Yoo et al showed that the caliber of the esophagus on early postoperative swallow was a useful parameter for predicting short-term clinical outcome after laparoscopic Heller myotomy and fundoplication. Postoperative esophageal symptoms were significantly more common in patients with a dilated esophagus as compared to a normal-caliber esophagus (60% vs. 15%) [17]. We found no relation between the presence of a megaesophagus and patient outcome.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Yoo et al showed that the caliber of the esophagus on early postoperative swallow was a useful parameter for predicting short-term clinical outcome after laparoscopic Heller myotomy and fundoplication. Postoperative esophageal symptoms were significantly more common in patients with a dilated esophagus as compared to a normal-caliber esophagus (60% vs. 15%) [17]. We found no relation between the presence of a megaesophagus and patient outcome.…”
Section: Discussioncontrasting
confidence: 38%
“…Many studies have looked at esophageal width as a prognostic factor [9,12,17], but none has used GEJ width for that purpose. Pechlivanides et al related the functional outcome of myotomy to the esophageal width (as measured 8 cm proximal to LES) on preoperative esophagogram and the extent of reduction in esophageal width after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There was a trend toward a higher incidence of intraoperative esophageal perforation and recurrent dysphagia in patients with prior PD treatment. Moreover, some studies [44][45][46][47] have demonstrated that reoperative laparoscopic HM can be undertaken safely (in experienced hands), and can result in good outcomes, with a similar level of success as that seen after primary myotomy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Esophageal myotomy has evolved from a transthoracic procedure to a minimally invasive transabdominal technique. Currently, laparoscopic anterior esophageal myotomy is the procedure of choice for patients with achalasia who represent an appropriate risk [6][7][8][9][10][11]. A partial fundoplication typically is performed simultaneously to reduce the incidence of symptomatic gastroesophageal reflux.…”
mentioning
confidence: 99%
“…However, the utility of this standard practice has not been evaluated extensively, and its clinical predictive value in a large cohort of patients is unknown [10].…”
mentioning
confidence: 99%